Penanda Molekuler Inter Simple Sequence Repeat untuk Menentukan Ketahanan Tanaman Jagung terhadap Penyakit Bulai - Polikarpia Wilhelmina Bani; Budi Setiadi Daryono; Purnomo Purnomo (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2017)
Downy mildew disease of maize, caused by the fungus Peronosclerospora maydis, can cause serious yield loss. Molecular markers-based method is usually performed to look for the variation of resistance in plants. In this study, 5 primers of inter simple sequence repeat (ISSR) was evaluated for molecular marker to determine maize resistance to downy mildew. The average polymorphic of 5 ISSR primers was 72.84%. Primer ISSR 808 (AG) 8C was able to differentiate resistant cultivar (cv Talenta) from susceptible cultivar (cv Pulut).